Kandungan vitamin C dan antioksidan lulur bunga telang (Clitoria ternatea L.) - Khusnita Pangesti, Yusni; Sudirga, Sang Ketut; Sudatri, Ni Wayan (Jurnal Biologi Udayana; Vol 27 No 2 (2023): JURNAL BIOLOGI UDAYANADO - 10.24843/JBIOUNUD.2023.v27.i02.p10, 2024)
Healthy skin is one of thing that related to beauty. Healthy skin can be treated by using body scrub. Body scrub can be made by using natural ingredients. Vitamin C is one of the natural ingredients that is often used as a body scrub ingredient and a natural antioxidant. A potential plant as body scrub ingredient is butterfly pea ( Clitoria ternatea L.) because butterfly pea has a high enough of vitamin C. This study aimed to find out the content of vitamin C and antioxidants in butterfly pea powder and butterfly pea body scrub, also find out the perception of respondents towards butterfly pea body scrub. The research design used to test vitamin C content and antioxidant inside body scrub was a completely randomized design with 6 variations of body scrub and 3 repetitions. Also carry out the organoleptic test, and hedonic test. Results of the research was analyzed by using ANOVA statistical tests and continued with Duncan test. The results of the analysis are displayed in tables. Butterfly pea powder has vitamin C content of 1.41 mg/100g and IC50 of 118.25 ppm which is medium grade. Vitamin C content in butterfly pea body scrub are consistent with the value of butterfly pea body scrub antioxidant activity with the highest grade found in the body scrub with 75% rice powder and 25% butterfly pea powder, while the lowest in the body scrub with 95% and 5% butterfly pea powder . The most preferred scrub is scrub with 75% rice powder and 25% butterfly pea powder.